The Impact of Accreditation on the Performance of Hospital Emergency Departments - Abolghasem Pourreza; Ali Mohammad Mosadeghrad; Parsa Zoleikani (Kerman University of Medical Sciences, 2017)
Background & Objectives: Accreditation, as a formal external evaluation system, has a critical role in improving quality, safety and effectiveness of hospital services. The aim of this study was to evaluate the effects of accreditation standards on the performance of Accident and Emergency (A&E) departments of hospitals in Sari, Iran. Methods: This cross-sectional descriptive - analytic study was carried out in eight hospitals in Sari, Iran. Information related to the accreditation scores and five performance indicators of A&E departments (i.e., average triage time, percentage of cardiopulmonary resuscitation failure, percentage of patients who were decided upon within 6 hours, percentage of patients sent out of the A&E department within 12 hours and percentage of patients left A&E department against the medical advice) in (March 2013 and March 2014) and (March 2014 and March 20115) were gathered form hospitals and accreditation office of Mazandaran University of Medical Sciences. Data were analyzed through SPSS (V.22) software and using descriptive and inferential statistics. Results: The mean scores of accreditation of A&E departments in 2013 and 2014 were 76% and 62.2% respectively. The differences between performance indicators of A&E departments in 2013 and 2014 were not statistically meaningful. There was no significant relationship between accreditation and the performance of A&E departments of hospitals. Conclusion: Accreditation did not improve A& E performance in Sari hospitals. Hence, there is a pressing need for improving hospital accreditation system including standards, methods and surveyors. Besides, hospital managers should use internal quality management systems to complement and strengthen the impact of external accreditation system in improving key performance indicators of hospitals. Keywords: Standard, Accreditation, Accident and emergency department, Key performance indicators, Hospital Citation: Pourreza A, Mosadeghrad AM, Zoleikani P. The Impact of Accreditation on the Performance of Hospital Emergency Departments. Journal of Health Based Research 2017; 3(3): 277-295.